Television and Empathy
XVII, 305 p. 1 illus.
Keywords: What is television’s capacity to elicit empathy? This book, Television and Empathy, brings together responses from a range of international scholars and interdisciplinary approaches. Television’s serialised form, ensemble casts and depth of storytelling has long granted viewers extended access to a diversity of perspectives. Meanwhile, interactive online technologies and platforms increasingly promise more personal and collective relationships with the small screen than ever before. With chapters exploring series from the UK and US, Australia, Iceland, Netherlands, South Korea and Spain, this cutting-edge collection responds to this juncture of television and affective theory. This collection is essential reading for upper undergraduates, postgraduates and researchers working in screen studies and audience studies, cognitive media theory, digital and cultural studies and psychology Michael Samuel is a Lecturer in Digital Film and Television and Co-Director of the Bristol Digital Game Lab at the University of Bristol, UK. He is the author of Northern Exposure: A Cultural History and co-editor of Streaming and Screen Culture in the Asia-Pacific and True Detective: Critical Essays on the HBO Series. Theresa Trimmel is a Lecturer in Film and Television at the University of Bristol, UK. Her research focuses on gender and television and her writings have been published in Mai: Feminism & Visual Culture, New Review of Film and Television Studies, and Communication, Culture, and Critique, among others.